Proposed Marketing Strategy For Work From Home Application By Telkom Indonesia (The Indonesian Journal of Business Administration, 2021)
PT. Telkom Indonesia is a state-owned enterprise that is engaged in the telecommunication and information technology sector. Since the dawn of COVID-19 pandemic, the majority of business sectors are migrating their workers to work from home (WFH). Meanwhile, Telkom Indonesia doesn’t have a WFH application in their product offering. The author of this study felt that the lack of WFH application is a missing opportunity for Telkom Indonesia to gain additional revenue from. This study is meant to understand what is the proper marketing strategy to market the WFH application.A strategic management process is used in this study to craft the best marketing strategy for the WFH application. The process starts from external and internal environment scanning and culminates into SWOT analysis. Segmenting, targeting, and positioning (STP) method used to choose which target market to tap into then a further analysis using TOWS matrix to choose suitable strategies given the opportunities or threat presented from the external factor; strength and weakness owned by the company.The proposed marketing strategy then formulated from the combination of the result of STP analysis and the TOWS analysis results in what is the best target segment to tap into and what is the suitable marketing strategy for the target segment. The following implementation program then formulated using the proposed marketing strategy.Keywords: Telkom Indonesia, marketing strategy, work from home, STP, TOWS, SWOT